Behavioural Economics Explanation: Trump's success and its impact for the next elections in Europe - Dominik Enste (Institut der deutschen Wirtschaft (IW), 2017)
Donald Trump is now the 45th president of the USA. Behavioral economics can explain why he was successful even though his positions are somewhat controversial. Furthermore, his success raises critical implications for Europe's next elections. Some of the main reasons for the success of populist politicians are explained.
Keywords: 330